Education About Occupational Health and Safety in The Company - Pandean, Marlyn M.; Sumarab, Evan Hizkia; Ali, Rizki Rhamadhan; Ante, Yesaya; Kesek, Marsekal Pratama (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Occupational safety and health (K3) is an important aspect in the industrial world that aims to protect workers from the risk of accidents and occupational diseases. Education about K3 in companies is an effective preventive step in creating a safe and healthy work environment. This paper aims to examine the effectiveness of K3 education programs in increasing worker awareness and compliance with safety standards. Therefore, companies are advised to integrate K3 education programs as part of company policies to create a safer and healthier work environment for all workers